If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12 = -4 + -2x Reorder the terms: 12 + 6x = -4 + -2x Solving 12 + 6x = -4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 12 + 6x + 2x = -4 + -2x + 2x Combine like terms: 6x + 2x = 8x 12 + 8x = -4 + -2x + 2x Combine like terms: -2x + 2x = 0 12 + 8x = -4 + 0 12 + 8x = -4 Add '-12' to each side of the equation. 12 + -12 + 8x = -4 + -12 Combine like terms: 12 + -12 = 0 0 + 8x = -4 + -12 8x = -4 + -12 Combine like terms: -4 + -12 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| (0)-3y=3 | | 7x+6=-6+x | | 2(f-7)=-18 | | F(x)=10*ln*7x | | 3(95+-6x)=x+-152 | | -10(s+1)=-81 | | 2(n-8)=72 | | p=5x+6x+3x+2 | | 12000=100x+300y | | 3(95-8x)=x-152 | | 3(t+5)=12 | | (9x^2+3x-4)+(x^2-6x)= | | 8(2l+4)=144 | | 44=-v/3 | | 2(a-7)=30 | | 25x-40=33x-27 | | (q-7)*3=18 | | 4g+2b=3m | | W/9=-43 | | x^2-72x+720=0 | | 12y-15/8-6y=10 | | x^2+y^2+3xy=2015 | | (12x-6x)/6x | | 165=5(4n+5) | | c-d=-2 | | 4/5x-7=25 | | Y^2+10Y+25+4Y^2+8Y+4=9y^2-6Y+1 | | 3x+27=-24x-6 | | 4/5-7=25 | | 5(3)-4y=0 | | cd+d=4 | | 9/10-1/10 |